Research on forced migration from the perspective of the psychology of religion: Opportunities and challenges - Grzymała-Moszczyńska, Halina (Archive for the psychology of religion, 2019)
The goal of our article is to present the subject of forced migration as a very interesting and socially relevant research field that could contribute to further development of the psychology of religion. We focus on further development of the toolbox of the psychology of religion, seeking further application of Sunden’s role theory and introducing new approaches originating from indigenous and environmental psychology. After a short review of existing research, new theoretical approaches, and methodologies are presented, along with suggestions for improving the validity of qualitative research pertaining to the role of religion at all stages of the migration process.